1990
DOI: 10.1213/00000539-199004000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Different Effects of Halothane and Enflurane on Diaphragmatic Contractility In Vivo

Abstract: We examined the effects of halothane and enflurane on diaphragmatic contractility in 12 anesthetized, mechanically ventilated dogs. The diaphragmatic force was assessed from transdiaphragmatic pressure (Pdi) developed at functional residual capacity against an occluded airway during cervical phrenic nerve stimulation. Animals were randomly assigned to two groups, a halothane group (n = 6) and an enflurane group (n = 6). The Pdi stimulus-frequency relationship was compared at anesthetic levels of 1, 1.5, and 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
16
0
2

Year Published

1991
1991
2013
2013

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 0 publications
1
16
0
2
Order By: Relevance
“…A study in dogs during propofol anaesthesia [17] detected a fall in TwPdi of 10% to 20%. Volatile anaesthetic agents have also been found to reduce diaphragm contractility in some animal studies [18,19,20], but not all [21].…”
Section: Discussionmentioning
confidence: 99%
“…A study in dogs during propofol anaesthesia [17] detected a fall in TwPdi of 10% to 20%. Volatile anaesthetic agents have also been found to reduce diaphragm contractility in some animal studies [18,19,20], but not all [21].…”
Section: Discussionmentioning
confidence: 99%
“…The diaphragm is the main inspiratory muscle and contributes to the 2/3 of the actual tidal volume [3], [4]. The effects of many inhalation (enflurane, halothane, isoflurane, sevoflurane) and injectable (propofol, thiopentone) anaesthetics on the respiratory function and more specifically on diaphragmatic contractility have already been studied in animals and humans [5], [6], [7], [8], whereas few data exist on the influence of opioids and methylxanthines [9], [10]. In all these studies, the diaphragmatic contractility was evaluated experimentally by measuring the trans-diaphragmatic pressure (P di ) after electrical stimulation of the phrenic nerves.…”
Section: Introductionmentioning
confidence: 99%
“…While enflurane depresses diaphragmatic function in a dose-dependent manner, halothane and isoflurane show little effect on it [7], [8], [11], [12] and sevoflurane has an intermediate effect [13], [14]. It has also been shown that halothane depresses P di and the electrical activity of the diaphragm in spontaneously breathing dogs [5].…”
Section: Introductionmentioning
confidence: 99%
“…The favorable recovery profile associated with propofol offers advantages over traditional anesthetic and sedative medications in clinical situations (1). Like volatile anesthetics (halothane, enflurane, isoflurane, and sevoflurane) (2)(3)(4)(5), propofol decreases contractility in nonfatigued and fatigued diaphragm (6,7). No studies have been reported evaluating the recovery from reduced diaphragmatic contractility caused by propofol.…”
mentioning
confidence: 99%